THE ROLE OF STAKEHOLDER PRESSURE IN MODERATING THE EFFECT OF GREEN INVESTMENT, CORPORATE GOVERNANCE AND CORPORATE GROWTH ON CARBON EMISSIONS DISCLOSURE - Murwaningsari, Etty; Riyanti, Yulia Eka (Penerbit Lafadz Jaya, 2023)
This study aims to determine the role of stakeholder pressure in moderating the effect of green investment, corporate governance and corporate growth on disclosure of carbon emissions. The data of this study use unbalance panel with multiple linear regression analysis which is operated through the eviews. The results of this study are green investment, company growth and the control variable firm size have a positive effect on disclosure of carbon emissions. In addition, stakeholder pressure is able to moderate the effect of green investment on disclosure of carbon emissions. However, corporate governance, profitability and company age control variables have no effect on disclosure of carbon emissions. The same thing happened to stakeholder pressure not being able to moderate the effect of corporate governance and company growth on disclosure of carbon emissions. These results provide implications for investors to consider disclosure of carbon emissions in making investments. The implications for regulators are expected to be able to formulate standards related to the disclosure of carbon emissions in more detail and to determine the number of directors who occupy a company.